Ibuprofen prevents the conjugative transfer of plasmid-mediated antimicrobial resistance genes - Guangfen Zhang; Chunli Li; Xiaofan Li; Yuanyuan Li; Yunbing Li; Xiangkun Zeng; Chen Xu; Shuyan Wu; Ning Dong (Journal of Global Antimicrobial Resistance)
Refractory infections caused by multidrug-resistant bacteria pose a significant threat to public health. Here we report that ibuprofen inhibits conjugation of the RP4 plasmid and plasmids from clinical strains carrying different resistance genes including mcr-1, blaNDM, blaKPC, tet(X4), and tmexCD1-toprJ1. Mechanistic studies suggest that ibuprofen reduces ATP production and inhibits conjugation-related genes. The inhibitory effect of ibuprofen on conjugation has significant clinical implications for preventing the spread of multidrug resistance, opening new therapeutic avenues to combat multidrug-resistant bacteria.